2020
DOI: 10.1007/s10068-020-00838-z
|View full text |Cite
|
Sign up to set email alerts
|

Verification of a novel glyceraldehyde-3-phosphate dehydrogenase capable of histamine degradation and its preliminary application in wine production

Abstract: The search for enzymes with histamine-degrading activity is of great interest, since it has great potential in the way of solving the problem of high histamine levels in food. In this study, the gene of a novel histamine-degrading enzyme, i.e., glyceraldehyde-3-phosphate dehydrogenase (GAPDH) from Lactobacillus plantarum was cloned and successfully expressed in Escherichia coli DH5a, with the recombinant host determined as histamine-degrading active. The recombinant GAPDH was then purified to homogeneity by am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Moreover, Jiang et al successfully expressed GAPDH in Escherichia coli for the first time and purified it. It was also found that recombinant GAPDH was highly resistant under both sulphate and ethanol stress, and the histamine in wine was broken down by 83.1-85.5% [67].…”
Section: Plantarummentioning
confidence: 99%
“…Moreover, Jiang et al successfully expressed GAPDH in Escherichia coli for the first time and purified it. It was also found that recombinant GAPDH was highly resistant under both sulphate and ethanol stress, and the histamine in wine was broken down by 83.1-85.5% [67].…”
Section: Plantarummentioning
confidence: 99%